Peningkatan Keterampilan Menulis Puisi Melalui Strategi Kreatif-Produktif Dengan Media Gambar Seri Siswa Kelas VSDN Gabugan 3 SragenTahun Ajaran 2015/2016 - Samnur, Nurul Febriani (2016)
PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI STRATEGI KREATIF-PRODUKTIF DENGAN MEDIA GAMBAR SERI SISWA KELAS V SDN GABUGAN 3 SRAGEN TAHUN AJARAN 2015/2016 Nurul Febriani Samnur, A510120026, Jurusan Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta, 2016, 64 Halaman. ABSTRACT The purpose of this research is to improve the skills of writing poetry through creative-productive strategy with the media image series fifth grade students of SDN Gabugan 3 Sragen of the school year 2015/2016. This research is a classroom action research. Subject of research that teachers and students comprised 20 students of five men and 15 women. Methods of data collection using observation, documentation and testing.The data analysis technique that is interactive analysis comprised data reduction, data description and give meaning. The results showed that through the creative-productive strategy with the media image series can improve students' skills of writing poetry class V SDN Gabugan 3 Sragen. It can be seen from the following results: an increase in the skill of writing poems on condition there is a new beginning 59.75% in cycle I experienced an increase of 68.87% and the second cycle increased by 80.12%. Means that already more than 80% of students who received grades above KKM (≥70) that meets the 80% achievement indicators. The study concluded that the increase in the skill of writing poetry through creative-productive strategy with the media image series fifth grade students of SDN Gabugan 3 Sragen of the school year 2015/2016. Keywords: poetry writing skills, creative-productive strategy, media image series